Identification of Physical and Mineralogical Properties of Riverbank Material at Sand Mining Landslide Sites of Kali Putih River, Blitar - Arlita Mey Hapsari; Dian Sisinggih; Andre Primantyo Hendrawan; Sri Wahyuni (U Karst, 2021)
Kali Putih River is a river that is often affected by the eruption of Mount Kelud. The resulting large deposits of volcanic sand materials cause exploitation through uncontrolled sand mines. This will have an impact on potential hazards caused by environmental damage; for example, there have been several cases of riverbank landslides. Based on previous studies, it is important to study the identification of physical characteristics and mineralogy of riverbank materials through laboratory testing. The Gs value was found to be within 2.650-2.697, which can be classified as gravel or sand. According to the AASHTO standard, the classification is coarse-grained soil. By USCS classification, all samples were determined as well-graded sand. Based on the JGS standard, these samples can be classified as Volcanic Soil (VS) and Volcanic Sand (SV). SEM results showed that the grain samples had low sphericity with angular to sub-angular and a bladed-oblate granular form. From X-RD analysis, the mineral composition of samples was dominated by anorthite (CaAl2Si2O8) and albite (Na(AlSi3O8)). Associated with Bowen's Reaction, these compounds are common in young materials when the weathering process is still progressing.